Outrage the five reasons why O. J. Simpson got away with murder - Bugliosi, Vincent 1934-2015 (Norton, 1996)
But in the Simposon case there was a mountain of incriminating evidence pointing inevitably and absolutely to the defendant's guilt. What happened? What went wrong? Much of that evidence, including some of the most vital pieces was never presented to the jury by the prosecutors; there were disastrous lapses in the prosecution's strategy, which allowed damaging defense testimony to go unchallenged; prosecutors Clark and Darden failed to stand up to the abuses of Judge Ito, thereby hurting their credibillity with the jury; the final summations of the prosecution were weakly constructed, listlessly argue, and, most unforgivably, inadequately prepared.
Keywords: Simpson, O. J. <1947-> -- Trials, litigation, etc; Simpson, Orenthal J. -- 1947-2024; Trials (Murder) -- California -- Los Angeles; Prozess